SAT0436 CROWNED-DENS SYNDROME: A RECENT CASE SERIES IN A SINGLE CENTRE IN THE UNITED KINGDOM. (June 2019) - Ma, Jianfei; Gonem, Rania; Lever, Elliott; Stratton, Richard; Singh, Animesh
Abstract : Background: The crowned dens syndrome is a rare presentation of Calcium pyrophosphate deposition disease. It is characterised by severe acute or recurrent neck pain associated with headache, fever and elevated inflammatory markers. CT usually demonstrates calcium pyrophosphate crystal deposition in the suspensory ligaments adjacent to the atlanto-axial joint. We are reporting a series of four patients presenting with sudden onset of neck pain and raised inflammatory makers over a 9 month period. Objectives: To raise awareness of crowned-dens syndrome, its clinical presentation, radiographic findings and management. Methods: Four patients' electronic patient records including history, clinical findings and treatment were reviewed. Imaging was discussed at a rheumatology/radiology multi-disciplinary meeting. Results: Four patients (2 female, 2 male) aged between 64 and 86 years presented with severe neck pain and stiffness. In all cases the onset of symptoms was less than a week prior to presentation and was associated with greatly restricted mobility. 2 patients had associated headache, arthralgia and myalgia. All patients had normal tone, power, reflexes and sensation on neurological examination. There was no pyrexia. Inflammatory markers were markedly raised with CRP ranging from 90-343 mg/L at presentation (Table 1 ). One patient had a neutrophilia. CT scan of the head was performed in each case and showed no evidence of subarachnoid haemorrhage, space occupying lesion or meningeal enhancement. PET-CT scan in all patients showed intense uptake around the atlanto-axial joint as well as calcification of the ligaments. All patients were commenced on a reducing regime of prednisolone starting at 40mg daily, tapering to 0mg over 6 weeks. Symptoms and inflammatory markers reduced on induction of steroids. Two patients suffered a relapse on reducing steroids and required further higher doses of steroid. Conclusion: Patients presenting with acute neck pain, headache and raised inflammatory markers require evaluation for an infective aetiology. Pyrophosphate disease of the atlanto-axial joint however, appears to be an increasingly recognised cause of this presentation. Awareness by acute physicians, rheumatologists and radiology colleagues is important, as the condition can be misdiagnosed as Giant Cell Arteritis, Polymyalgia Rheumatica or meningitis; in order to avoid unnecessary investigations and delay in initiating the appropriate treatment. The condition is steroid responsive. References: [1] Heck A, Nolan N, Rojas-Moreno C, Crowned Dens Syndrome: Calcium Pyrophosphate Deposition Disease Masquerading as Osteomyelitis. J Rheumatol. 2018Oct;45(10):1422-1423 [2] Ledingham D, Cappelen-Smith C, Cordato D, Crowned dens syndrome. Pract Neurol. 2018Feb;18(1):57-59 [3] Tagami S, Inokuchi R, Awaji K, Maehara H, Yamaguchi Y, Nakajima S, Crowned dens syndrome and interspinous ligament inflammation due to calcium pyrophosphate deposition in an elderly man. Spine J. 2016Jul;16(7):e453-4 Disclosure of Interests: None declared